Financial access and digital services within agri-food value chains in Uganda - Adong, Annet; Ambler, Kate; Bloem, Jeffrey R.; de Brauw, Alan; Wagner, Julia (International Food Policy Research Institute, 2023)
Agri-food value chains represent an important element of food systems and economies around the world. For example, intermediary agri-food value chain actors—those operating enterprises that transport and transform food from the farmgate to retailers—account for a substantial share, often between 60 and 75 percent, of value-added produced by the entire agricultural sector of an economy.